Sign Pattern for Generalized Inverses - Bu, Changjiang; Sun, Lizhu; Wei, Yimin (Mathematics professor) (EDP Sciences, 2021)
This book addresses recent developments in sign patterns for generalized inverses. The fundamental importance of the fields is obvious, since they are related with qualitative analysis of linear systems and combinatorial matrix theory. The book provides both introductory materials and discussions to the areas in sign patterns for Moore-Penrose inverse, Drazin inverse and tensors. It is intended to convey results to the senior students and readers in pure and applied linear algebra, and combinatorial matrix theory. Changjiang BU is a Professor at the College of Mathematical Sciences, Harbin Engineering University, who works on the graph theory and generalized inverses. He is the author of more than 100 papers in the international journals and one monograph. Lizhu SUN is an Associate Professor at the College of Mathematical Sciences, Harbin Engineering University, who works on the graph theory and multilinear algebra. She is the author of 25 research papers. Yimin WEI is a Professor at the School of Mathematical Sciences, Fudan University, who works on the numerical linear algebra and multilinear algebra. He is the author of more than 150 papers in the international journals and six monographs published by Science Press, Elsevier, Springer and World Scientific., etc.